1996
DOI: 10.1111/j.1442-200x.1996.tb03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of acute glomerulonephritis in children: Observed association with the T1 subtype of group A streptococcal infection in Northern Kyushu, Japan

Abstract: Group A streptococcal infection is associated with the occurrence of acute glomerulonephritis (AGN) and rheumatic fever (RF). A surveillance study in the Saga area, in northern Kyushu, Japan, showed a small variation in the reported number of group A streptococcal infections in the period 1988–94. However, of the AGN cases reported in this period, more than half were observed in 1992. In order to examine whether some change had occurred in the serotype distribution of Streptococcus pyogenes during the period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…1). In the study of the Saga area in Japan by Masuyama et al , the number of patients with APSGN increased in 1992, while the total number of patients with group A streptococcal infections remained almost constant 9 . They concluded that the T1 subtype was related to the outbreak of APSGN as confirmed epidemiologically.…”
Section: Discussionmentioning
confidence: 95%
“…1). In the study of the Saga area in Japan by Masuyama et al , the number of patients with APSGN increased in 1992, while the total number of patients with group A streptococcal infections remained almost constant 9 . They concluded that the T1 subtype was related to the outbreak of APSGN as confirmed epidemiologically.…”
Section: Discussionmentioning
confidence: 95%
“…11 Outbreaks of the disease coincide with economic decline, poor hygiene, and insufficient medical care 512-14 Resurgence of APGN, although to a lesser extent, has also been noted in Japan, Western Europe, and North America 19 15 The number of patients in this epidemic in Armenia is even more impressive when taking into account the small population (three million) of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the association of emm types 1, 3, and 49 with invasive disease and emm types 2, 4, 6, 12, and 44/61 with superficial disease (46,58,59). Additionally, some emm types are associated with particular GAS disease manifestations such as ARF (e.g., emm types 1, 3,5,6,11,12,14,17,18,19,24,27,29,30,32, and 41), APSGN (e.g., emm types 1, 4, 12, 49, 55, 57, and 60), and puerperal sepsis (emm type 28) (60).…”
Section: Epidemiology Of Gas Infectionsmentioning
confidence: 99%
“…Several studies had noted a reduction in GAS disease burden in industrialized countries in the mid-20th century (11)(12)(13)(14). However, in the last 50 years, there have been widespread reports of significant outbreaks of ARF (15,16), APSGN (17,18), GAS invasive disease (14,(19)(20)(21), puerperal sepsis (22)(23)(24), and scarlet fever (25,26).…”
mentioning
confidence: 99%